PENGARUH KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU SENI BUDAYA DI KABUPATEN LAMPUNG TIMUR TERHADAP HASIL MENGAJAR SISWA SEKOLAH MENENGAH PERTAMA NEGERI TAHUN PELAJARAN 2025/2026 - Kadar Lumintu Wati; Sutrisni Andayani; Marzuki Noor (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The mismatch between teachers' educational backgrounds and the subjects they teach, particularly in Cultural Arts, has been a persistent issue in East Lampung Regency. This study aims to analyze the influence of pedagogical competence and professional competence of Cultural Arts teachers on student learning outcomes in public junior high schools. A quantitative approach with an explanatory survey method was employed. The population comprised 50 Cultural Arts teachers from six public junior high schools across four districts, and a sample of 35 teachers was selected using simple random sampling. Data were collected using Likert-scale questionnaires (1-4) that had been tested for validity (Pearson product-moment) and reliability (Cronbach's Alpha). Multiple linear regression analysis was conducted after normality, homogeneity, and linearity tests. The results indicate that: (1) pedagogical competence has a positive and significant effect on student learning outcomes (t-count = 3.083 > t-table = 2.037; Sig. = 0.004); (2) professional competence also has a positive and significant effect (t-count = 3.018 > t-table = 2.037; Sig. = 0.003); (3) simultaneously, both variables significantly affect learning outcomes (F-count = 12.581 > F-table = 3.29; Sig. = 0.000) with a coefficient of determination R² = 0.869, meaning that 86.9% of the variation in student learning outcomes is explained by pedagogical and professional competence. This study recommends the placement of teachers according to their academic backgrounds, integrated training programs, clinical supervision, professional learning communities, and partnerships with local artists.